DEVELOPMENT OF SOLAR ENERGY HARVESTER FOR INTERNET OF THINGS - MD ROSLAN, FARAH FARHANA (2018)
Currently, Internet of Things (IoT) has high demand all across the globe as the technology is rapidly evolving. IoT is used to provide real time data monitoring for application via the Internet. However, a stand-alone IoT needs a continuous power supply. The current use of rechargeable batteries requires high maintenance, cost and energy. Hence, solar energy harvester is the most preferred option in supplying the power required as it has the maximum power density generated compared to the other energy harvesters. This project focus on using a suitable power management scheme and energy storage solution of solar energy harvester for IoT. In order to achieve this, the solar energy harvester system is designed to have a battery charger with Maximum Power Point Tracking (MPPT) application to ensure that it can extract the maximum amount energy generated by the solar module. Other than that, the use of Nickel-Metal Hydride (NiMH) rechargeable batteries as energy storage will also guarantee a higher efficiency solar energy harvester system so that there will be no energy wasted. Consequently, the solar energy harvester system for this project will have a high efficiency as the result of good power management scheme and suitable energy storage solution for the application of remote IoT.